Corporate Social Responsibility Disclosure: Tax Agresiveness Indication? - Muhammad Alif Kurniawan; Mienati Somya Lasmana; Santi Novita (Jurnal Reviu Akuntansi dan Keuangan, 2020)
The purpose of this study to test whether Corporate Social Responsibility  disclosure can be used as a firms’ indication of the tax aggressiveness. Unlike the previous study, this paper uses both Effective Tax Rate Differences and Current Effective Tax Rate to provide the degree of aggressiveness. Besides, it compares among industries in Indonesia. The independent variable of this research is Corporate Social Responsibility disclosure measured by the Corporate Social Responsibility Disclosure Index based on the GRI G4 standard. The sample of this research is companies listed on the Indonesia Stock Exchange during the 2014-2018 period, except for the financial and construction sector. With 506 observations, the results of this research indicate that Corporate Social Responsibility disclosure has a significant effect on tax aggressiveness. The research implication provides the awareness to the tax authority that a good reputation of social responsibility can be a sign of tax aggressiveness existence. In addition, the result suggests that industry type is needed to be considered relate to taxation strategies.